The flow of peoples: international migration as a revolutionary force - Chesnais, Jean-Claude (Universidad ESAN. ESAN Ediciones, 2008)
History shows that migration usually moves from areas where population is growing fast to regions where this increase is slower. At present immigration from poor regions to richer coun tries outstrips emigration from developed countries. A century ago in Europe and now in the poorest countries migration has relieved tensions bred by declining mortality and accelerating popula tion growth. The map of international migration changes from decade to decade as each country's demographic transition matures. Although historical migration ﬂows still continue this will not lead to a demographic explosion as fertility rates have declined signiﬁcantly and aging population increases all over the world. World population is estimated to remain stagnant at around 8 thousand million before it decreases slowly through this century. Thus migration raises the challenge of a global multiethnic society.

La historia demuestra que por lo general la migración parte de zonas de rápido crecimiento poblacional con destino a regiones donde este aumento es más lento. Actualmente la inmigración procedente de las regiones pobres a los países más ricos supera la emigración de los países desarrollados. En Europa hace un siglo y en los países más pobres hoy la migración ha aliviado las tensiones creadas por la disminución de la mortalidad y el aumento del ritmo de crecimiento de la población. El mapa de la migración internacional cambia de década a década según madura la transición demográfica de cada país. Sin embargo los flujos migratorios históricos todavía no han terminado aunque no habrá explosión demográfica pues la fecundidad decrece de manera notoria en el mundo entero junto con el envejecimiento de la población. Se estima que el número de habitantes del planeta podría estabilizarse en torno a los 8 mil millones antes de decrecer lentamente durante este siglo. Así la migración plantea el reto de una sociedad multiétnica global
Keywords: Migratory flows; Immigration; Flujos migratorios; Demographic transition; Inmigración; Transición demográfica; Generation replacement level; Nivel de reemplazo generacional; https://purl.org/pe-repo/ocde/ford#5.02.04